2010
DOI: 10.1085/jgp.201010519
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of cholesterol and analogs to modulate BK channels points to direct sterol–channel protein interactions

Abstract: The activity (Po) of large-conductance voltage/Ca2+-gated K+ (BK) channels is blunted by cholesterol levels within the range found in natural membranes. We probed BK channel–forming α (cbv1) subunits in phospholipid bilayers with cholesterol and related monohydroxysterols and performed computational dynamics to pinpoint the structural requirements for monohydroxysterols to reduce BK Po and obtain insights into cholesterol’s mechanism of action. Cholesterol, cholestanol, and coprostanol reduced Po by shortening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 71 publications
(172 reference statements)
5
76
1
Order By: Relevance
“…4), indicating that the effect of cholesterol is not due to a nonspecific membrane effect, but rather to a stereospecific binding site. Similar results with other channels, including inward-rectifier K ϩ channels and large-conductance voltage/Ca 2ϩ -gated K ϩ channels, have also been interpreted to mean that the effect of cholesterol are not due to an indirect modification of lipid bilayer properties, but rather to a stereospecific interaction at the surface of the protein (19,32). We consequently explored rTRPV1 for possible cholesterolbinding sites.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…4), indicating that the effect of cholesterol is not due to a nonspecific membrane effect, but rather to a stereospecific binding site. Similar results with other channels, including inward-rectifier K ϩ channels and large-conductance voltage/Ca 2ϩ -gated K ϩ channels, have also been interpreted to mean that the effect of cholesterol are not due to an indirect modification of lipid bilayer properties, but rather to a stereospecific interaction at the surface of the protein (19,32). We consequently explored rTRPV1 for possible cholesterolbinding sites.…”
Section: Discussionsupporting
confidence: 67%
“…Epicholesterol (Fig. 1B) (Steraloids Inc., Newport, RI) was added to the membrane by incubating the patch with 10:1 M␤CD:epicholesterol (0.08 mg/ml) (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with these observations, it was shown more recently that ent-cholesterol, an enantiomer of cholesterol (17), has no effect either on KirBac1.1 or on Kir2.1 function (18). Differential effects of cholesterol analogues on channel function were also demonstrated in several other types of ion channels, including the nicotinic acetylcholine receptor (19), BK channels (20), and TRPV1 channels (21). Most recently, our laboratory has shown that cholesterol binds to purified KirBac1.1 channels and that cholesterol-KirBac1.1 binding is essential for the inhibitory effect of cholesterol on channel activity (22).…”
mentioning
confidence: 53%
“…For proper comparisons with previous data obtained by us (17,20,21,25) and others (19,22,31), studies were conducted at room temperature (20 -25°C).…”
Section: ϫ2mentioning
confidence: 99%
“…In a recent structure-activity relationship study of CLR and analogs on recombinant Slo1 channels cloned from rat cerebral artery myocytes (Cbv1) and reconstituted into a bare, two-species phospholipid bilayer, we demonstrated that CLR inhibition of BK P o was defined by strict structural requirements, including the ␤ configuration of a CLR single polar group at C3 and, more importantly, enantiospecificity of the CLR molecule, suggesting CLR recognition by a protein surface. Thus, we hypothesized that the BK channel-forming subunit contained a region(s) that specifically sensed membrane CLR presence, leading to BK P o reduction (25).…”
mentioning
confidence: 99%